Surface acoustic wave (SAW)-induced synthesis of HKUST-1 with different morphologies and sizes. Issue 45 (30th October 2018) - Xu, Chaoping; Wang, Chaohui; Zheng, Tengfei; Hu, Qiao; Bai, Cheng
Abstract : Metal organic frameworks (MOFs) are porous materials that have wide application prospects. Abstract : Metal organic frameworks (MOFs) are porous materials that have wide application prospects. In this study, a novel, facile, rapid, and environmentally friendly technology that uses surface acoustic waves (SAWs) as an energy source to induce the synthesis of HKUST-1 crystals in a droplet is presented. The acoustic streaming induced by SAWs has significant influence on the morphology and size of HKUST-1 crystals. By increasing the input power of SAWs, the kinetic effect of SAWs can improve the supersaturation of crystal growth units. Therefore, the HKUST-1 crystals with higher surface-energy faces and smaller sizes are generated. Moreover, we also researched the temperature trends with and without SAWs to further investigate the kinetic effect of SAWs to control the morphology and size of HKUST-1 crystals.